Development of thermoplastic elastomers based on maleated ethylene propylene rubber (m-EPM) and polypropylene (PP) by dynamic vulcanization (eXPRESS Polymer Letters)
Dicumyl peroxide (DCP)-cured thermoplastic vulcanizates (TPVs) based on blends of maleated ethylene propylene rubber (m-EPM) and polypropylene (PP) using maleated-PP as a compatibilizer have been developed. Physical properties of these TPVs change significantly with concentrations of DCP and rubber/plastic blend ratios. Important correlations were obtained from rheometer delta torque values with various physical properties of the TPVs like tension set and crosslink density etc. Wide angle X-ray diffraction study confirms that concentration of DCP has a strong influence on the crystallinity of PP, which might affect the final physical properties of TPVs. The recyclability and ageing characteristics of these TPVs are also found excellent.